Tahafut al-Falasifah as a Critique of Paradigms: A Philosophical Analysis from the Perspective of Modern Science - Nurhuda, Abid; Nawawi, Abdul Muid (Yayasan Pendidikan Bustanul Ulum Mojokerto, 2025)
This study attempts to reread Al-Ghazali's Tahafut al-Falasifah not merely as a theological polemic text, but as a critique of scientific paradigms that has profound relevance to modern philosophy of science. Al-Ghazali's critique of rationalist claims, particularly regarding causality, the eternity of the world, and the limitations of reason, is positioned as an attempt to shake the established epistemic foundations of his time. A qualitative-comparative approach is used by analyzing the primary text of Tahafut hermeneutically, then connecting it with the thoughts of modern philosophers such as David Hume, Karl Popper, and Thomas Kuhn. The results of the study show that Al-Ghazali had already presented an epistemological awareness that aligns with the discourse of the paradigm shift in science. He emphasized that causal relationships are not absolute certainties, but rather habits that can change according to transcendental will. This perspective finds resonance in the development of contemporary science, particularly in quantum physics and the philosophy of science, which emphasize the tentative nature of knowledge. Furthermore, Al-Ghazali's paradigm critique also carries ethical implications: knowledge must always be based on moral values and spiritual awareness to avoid being trapped in scientific arrogance. Thus, Tahafut al-Falasifah can be understood as a laboratory for epistemological criticism that remains relevant for building a paradigm of modern science that is humble, reflective, and humanity-oriented. This research emphasizes the importance of integrating revelation, reason, and science in formulating a new direction for Islamic philosophy and its contribution to the global discourse on the philosophy of science.